(untitled) (Texas Journal of Engineering and Technology, 2023)
Hydraulic fracturing is the most effective way to increase gas recovery in the development of reservoirs with low reservoir properties.After hydraulic fracturing, the well flow rate, as a rule, increases sharply. The method allows to "revive" idle wells, where oil or gas production by traditional methods is no longer possible or unprofitable.